U.K. Small Firm Bankruptcy Prediction: A Logit Analysis of Financial Trend-, Industry-, and Macro-Effects - Robert C. Cressy (Journal of Small Business Finance, 1992)
Much work has been done in the last two decades to estimate the determinants of bankruptcy of large firms. Very little work appears to have been attempted in the area of small firm bankruptcy. This paper goes some way to remedy the deficiency by estimating conditional logistic probability regressions for small firm bankruptcy on a recently constructed U.K. accounts database.
Keywords: L25; G33; 650; Bankruptcy; UK; Financial Trend; Industry Effects